Clinical and Radiographic Evaluation of Brånemark Implants with an Anodized Surface following Seven-to-Eight Years of Functional Loading - David Gelb; Bradley McAllister; Pirkka Nummikoski; Massimo Del Fabbro (International Journal of Dentistry)
The aim of this study was to evaluate the clinical and radiographic long-term outcomes of dental implants with an anodized TiUnite surface, placed in routine clinical practice. Two clinical centers participated in the study. One hundred and seven implants (80 in the maxilla and 27 in the mandible) in 52 patients were followed in the long term. Both one- and two-stage techniques were used for 38 and 69 implants, respectively. Thirty-eight single tooth restorations and 22 fixed partial prostheses were delivered, according to a delayed loading protocol, within 4 to 12 months since implant placement. All implants were stable at insertion and at the long-term follow-up visit, which occurred between 7 and 8 years of functional loading. The mean followup was 7.33±0.47 years. The mean marginal bone level change at the long-term followup as compared to baseline was 1.49±1.03 mm. No implant failure occurred. Healthy peri-implant mucosa was found around 95% of implants, whereas 91% of implants showed no visible plaque at the implant surfaces at the long-term followup. The study showed that dental implants with the TiUnite anodized surface demonstrate excellent long-term clinical and radiographic outcomes.